2004
DOI: 10.1002/ar.a.20003
|View full text |Cite
|
Sign up to set email alerts
|

Granule types and their morphological changes in terminal cluster and acinar cells in the late pre‐ and early postnatal rat sublingual gland

Abstract: The developmental characteristics of serous cells appearing in the rat sublingual gland from the late prenatal to the early postnatal period were investigated in this study. Particular attention was paid to the morphological changes observed in the secretory granules at the histochemical and ultrastructural level. On prenatal day 18, granules with homogeneous high electron density (Type I granules), and mottled granules (Type II granules) with heterogeneous electron density appeared in the narrow luminar cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…These results are also consistent with observations of postnatal rat palatine glands which suggested that the increased electron density of secretory granules in acinar cells at PN10 is due to the presence of phospholipid (Okamoto et al, 2008). Moreover, the appearance of a large number of cells with highly electron-dense granules agrees with reports on the developing sublingual glands (Redman and Ball, 1979;Kikuchi et al, 2004). Wolff et al (2002) suggested that the mucous and serous cells follow separate pathways of differentiation, and that the cells containing mixed granules are developing mucous cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are also consistent with observations of postnatal rat palatine glands which suggested that the increased electron density of secretory granules in acinar cells at PN10 is due to the presence of phospholipid (Okamoto et al, 2008). Moreover, the appearance of a large number of cells with highly electron-dense granules agrees with reports on the developing sublingual glands (Redman and Ball, 1979;Kikuchi et al, 2004). Wolff et al (2002) suggested that the mucous and serous cells follow separate pathways of differentiation, and that the cells containing mixed granules are developing mucous cells.…”
Section: Discussionsupporting
confidence: 91%
“…Wolff et al () suggested that the mucous and serous cells follow separate pathways of differentiation, and that the cells containing mixed granules are developing mucous cells. On the other hand, Kikuchi et al () suggested that the granules in the secretory cells of the developing rat sublingual gland change from the serous to the mucous type during the process of granule production. In the submandibular glands, the proportion of mucous to serous substances in the acinar cells increased with the maturation during postnatal development (Yamashina & Mizuhira, ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that the dominant acinar cell type in developing parotid and sublingual glands is converted from the late prenatal to the early postnatal period. In neonate sublingual glands, acinar cells have numerous serous granules that are replaced by mucous granules according to the developmental stage [ 8 ]. The lack of acinar cell apoptosis in these glands indicates that most of the acinar cells transform, but they are not replaced by cells of another type.…”
Section: Histology and Organogenesis Of The Salivary Glandsmentioning
confidence: 99%
“…More recently, it was reported that the cells containing the mucous‐like granules or mixed granules are the precursors of the mucous acinar cells of the rat sublingual gland (Wolff et al, ). Kikuchi et al, () noticed that the majority of the granules replaced the mucous granules through transforming‐type granules in the developing rat sublingual gland. Therefore, they also suggested that most of the serous cells in the developing rat sublingual gland might have changed in to mucous cells.…”
Section: Discussionmentioning
confidence: 99%